A Bee Colony Optimization Approach for Mixed Blocking Constraints Flow Shop Scheduling Problems. (22nd November 2015) - Khorramizadeh, Mostafa; Riahi, Vahid
Abstract : The flow shop scheduling problems with mixed blocking constraints with minimization of makespan are investigated. The Taguchi orthogonal arrays and path relinking along with some efficient local search methods are used to develop a metaheuristic algorithm based on bee colony optimization. In order to compare the performance of the proposed algorithm, two well-known test problems are considered. Computational results show that the presented algorithm has comparative performance with well-known algorithms of the literature, especially for the large sized problems.